Question #c8498

1 Answer
May 3, 2017

First one is -8(2t-5)(t-1)
Second one is -4.9(t-1)(t-4)
Last one is -4.9(t-40)(t-10)

Explanation:

Factor a number out of the equation, but make sure that the values are whole numbers. That's why we cannot factor -16, it'll turn them into fractions.
-8(2t^2-7t+5)
After that, use the cross method to solve the expression in the bracket. I can't really do the crosses, so I'll just multiply across.
2t*-1=-2
t*-5=-5t
Add the results together to see if they equal -7t
-5t+(-2t)=-7t
Now, just bracket the expressions that are diagonal of each other, so if 2t and -5 are opposite of each other, bracket them together, hence, the cross method.

*NOTE - Normally, you would multiply diagonally and bracket the terms across, but I can't do that with these maths symbols, so I multiply across and bracket diagonally.
-8(2t-5)(t-1)

Apply the same method for the second and last one.
If you factor the -4.9 out, you end up with whole numbers.
-4.9(t^2-5t+4)
t*-4=-4t
t*-1=-t
-t+(-4t)=-5t
-4.9(t-1)(t-4)

And the last one:
-4.9(t^2-50t+400)
(There are many ways to calculate 400 with multiplication, so just trial and error)
t*-40=-40t
t*-10=-10t
-10+(-40t)=-50t
-4.9(t-40)(t-10)